Cautions of Using Allele-Based Tests Under Heterosis - Omolo, Bernard; Zhang, Hongmei; Karmaus, Wilfrieed (International Journal of Statistics in Medical Research, 2013)
:In genetic studies, heterotic effects are commonly assessed as dominant, additive, or recessive effects for a given genetic marker. However, the distorting effect of heterosis on statistical tests is non-trivial. An inheritance model needs to be carefully chosen to achieve highest testing power. We assess this through simulations via allele- and genotype-based tests. Chi-square test statistics for different inheritance models are formulated as a function of relative risks and allele frequencies. The results indicate that testing power from the commonly used allele-based tests can be substantially diminished by heterosis. Assessing the existence of heterosis is thus recommended to avoid false negative findings.